The Negative Effect of Market Orientation on SMEs' Marketing Performance in The Creative Economy Sector, and How Innovation Mediating it - Sarli Rahman; Budiyanto Budiyanto; Suwitho Suwitho (International Journal of Economics Development Research (IJEDR), 2021)
There are problems with the performance of SMEs in the creative economy sector in Indonesia. At least about 34% to 35% of SMEs in the creative economy sector experience problems related to marketing and demand. So, this study aims to prove the effect of market orientation on the SMEs' marketing performance of the creative economy sector and to prove the mediate roles of innovation. By using a sample of 200 respondents, and Structural Equation Modeling (SEM - AMOS) analysis technique, surprising results were obtained. The results are that market orientation affects marketing performance negatively. However, product innovation and process innovation can be a solution for this.